“SHARQ TARONALARI” - INTERNATIONAL MUSIC FESTIVAL IN SAMARKAND - Ikromova Farangis Yigitali kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article shows that the international music festival is a powerful factor in the spiritual health of the Eastern world, including the musical values of the Uzbek people, in order to set their development on the right track.